2020
DOI: 10.20944/preprints202005.0144.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong>Pyridoxal 5'-phosphate to mitigate immune dysregulation and coagulopathy in COVID-19</strong>

Abstract: Although most cases of COVID-19 are paucisymptomatic, severe disease is characterized by immune dysregulation, with a decreased type I interferon response, increased inflammatory indicators, surging IL-6, IL-10 and TNF&alpha; suggestive of cytokine storm, progressive lymphopenia, and abnormal blood clotting. Factors determining susceptibility to severe disease are poorly understood, although mortality correlates with increasing age and co-morbidities including diabetes and cardiovascular disease (CVD). Pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Dysregulation of immune responses and increased risk of coagulopathy have also been noted among COVID-19 patients. In a recent preprint it is suggested that PLP supplementation mitigates COVID-19 symptoms by regulating immune responses, decreasing pro-inflammatory cytokines, maintaining endothelial integrity and preventing hypercoagulability [22]. In fact, it was shown three decades ago that PLP levels reduce abnormalities in platelet aggregation and blood clot formation [23].…”
Section: Vitamin B 6 (Pyridoxal 5 ′ -Phosphate Pyridoxine)mentioning
confidence: 99%
“…Dysregulation of immune responses and increased risk of coagulopathy have also been noted among COVID-19 patients. In a recent preprint it is suggested that PLP supplementation mitigates COVID-19 symptoms by regulating immune responses, decreasing pro-inflammatory cytokines, maintaining endothelial integrity and preventing hypercoagulability [22]. In fact, it was shown three decades ago that PLP levels reduce abnormalities in platelet aggregation and blood clot formation [23].…”
Section: Vitamin B 6 (Pyridoxal 5 ′ -Phosphate Pyridoxine)mentioning
confidence: 99%
“…The utilization of vitamin B6 rapidly increases under inflammatory conditions, and COVID-19 patients probably may have vitamin B6 deficiency (156). Vitamin B6 downregulated the pulmonary inflammation by inhibiting macrophage activation, as reduced production of IL-1β, IL-6, and TNF-α in macrophages challenged with LPS of mice (155). In a rat model of systemic inflammation, orally administered 500 mg/kg riboflavin and 600 mg/kg thiamine increased the anti-inflammatory activity of dexamethasone, along with reducing TNF-α and IL-6 production (157).…”
Section: B Vitaminsmentioning
confidence: 99%
“…Vitamin B6 levels and the severity of inflammatory reactions are inversely correlated (154,155). The utilization of vitamin B6 rapidly increases under inflammatory conditions, and COVID-19 patients probably may have vitamin B6 deficiency (156).…”
Section: B Vitaminsmentioning
confidence: 99%
“…When there is PLP deficiency, this lyase is inhibited, and when the lyase is deficient, lymphocytes are arrested in secondary lymphatic organs and in places where inflammatory processes take place [ 5 , 6 ]. This leads to lymphopenia and immunosuppression as well as to local exacerbation of inflammatory processes and to an increase in the secretion of pro-inflammatory cytokines [ 5 ].…”
Section: Some Metabolic Functions Of Plp In Healthmentioning
confidence: 99%
“…Descriptions of the mechanisms of these reactions can be found in any textbook on biochemistry. The key pathways for human health with the regulatory involvement of vitamin B6 include the metabolism of sphingosine phosphate [ 5 ], tryptophan catabolism [ 6 ], and the action of the transcription factor NF-κB. According to the latest research, it has the effect of reducing inflammation in the body by influencing the activity of inflammasomes and specifically its component, the NLRP3 sensory protein [ 7 ].…”
Section: Introductionmentioning
confidence: 99%